Developing A Digital-Based Library To Enhance Educational Knowledge Among Students - Rizky, Muhammad Al; Hartati, Hartati; Syafaruddin, Syafaruddin (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
This Education serves as a means or pathway for individuals to unlock and develop their potential through the learning experiences they acquire. A type of learning resource is the digital library, which represents an innovative facet of library advancement designed to engage a broader audience. This study emerged from the absence of e-books or digital resources for high school students, specifically those at State Vocational High School 2 Palembang. The research follows a developmental approach using the Research and Development (R&D) method. The study employs two types of instruments: a product validity sheet addressed to both media and material experts, and an instrument evaluating practicality and effectiveness aimed at students, particularly those in class X at State Vocational High School 2 Palembang. The research yields a Digital Library Website for Physical Education, Sports, and Health subjects, deemed suitable as a learning resource based on validation results. Material experts assigned an average score of 4.4, categorizing it as "very practical," while media experts rated it 4.6, also in the "very practical" category. Small-scale trials obtained an average score of 4.1, and large-scale trials achieved an average of 4.175, both falling into the "very practical" category. These outcomes affirm the practicality of digital-based libraries for educational use.